Gendered post-harvest losses among informal retailers in Egypt - Murphy, Seamus (WorldFish, 2017)
Presented by Seamus Murphy (World Fish), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.